Effects of dosing non-toxigenic Clostridia on the bacterial populations and immunological responses in the intestinal tract of lactating dairy cows - Kim, Hye Won; Kim, Na Kyung; Thompson, Jesse; de Jesus, Mackenzie; Rehberger, Josh; Rehberger, Thomas; Smith, Alexandra Helena; Mackie, Roderick Ian (Frontiers in Microbiology, 2023)
Understanding the effects of dosing non-toxigenic Clostridia to cows is rare and has received little attention so far. In the present study, a total of eight lactating dairy cows were divided in two groups: control (n=4) or Clostridia challenged (oral supplementation of five diverse strains of Paraclostridium bifermentans, n=4). Bacterial communities were analyzed by qPCR and next-generation sequencing (NGS) in the buccal mucosa as well as digesta and mucosal samples of the gastrointestinal (GI) tract from rumen to rectum (10 compartments), as well as fecal samples. Transcriptomic analysis of barrier and immune-related gene expression was performed on rumen, jejunum, and liver samples. We observed increased microbial populations with the Clostridia challenge in the buccal tissues and the proximal GI tract (forestomach), correlating with Clostridial loads in the feed. Otherwise, there were no significant differences in microbial populations (P > 0.05) throughout the distal part of the GI tract. The NGS approach, however, revealed that the Clostridial challenge changed the relative abundance of gut and fecal microbiota. In particular, in the challenge group, no Bifidobacterium was observed in the mucosa-associated microbiota and abundance of Proteobacteria increased in the feces. These results indicated potential adverse effects of Clostridia to cow health. In general, immune responses to the Clostridial challenge were weak. However, transcriptional analysis revealed the down-regulation of junction adhesion molecule encoding gene (-1.44 of log2 fold-change), which might impact intestinal permeability.